Ion channel blockers as antimicrobial agents, efflux inhibitors, and enhancers of macrophage killing activity against drug resistant mycobacterium tuberculosis - Machado, Diana (2018)
Given the ability of M. tuberculosis to survive as an intracellular pathogen and its propensity to develop resistance to the existing antituberculosis drugs, its treatment requires new approaches. Here the antimycobacterial properties of verapamil, thioridazine, chlorpromazine, flupenthixol and haloperidol were investigated against a panel of drug resistant M. tuberculosis strains, both in vitro and on human-infected macrophages. These compounds are efflux inhibitors that share among them the characteristic of being ion channel blockers. In vitro, all compounds exhibited synergistic inhibitory activities when combined with isoniazid and rifampicin, and were able to inhibit active efflux, demonstrating their role as efflux inhibitors. Gene expression analysis showed that M. tuberculosis efflux genes were overexpressed in response to antibiotic exposure, in vitro and within macrophages, irrespective of their resistance pattern. These compounds displayed a rapid and high killing activity against M. tuberculosis, associated with a decrease in intracellular ATP levels demonstrating that the bactericidal action of the ion channel blockers against M. tuberculosis clinical strains is associated with their interference with energy metabolism. The compounds led to a decrease in the intracellular mycobacterial load by increasing phagosome acidification and activating lysosomal hydrolases. The results presented in this study enable us to propose the following mechanism of action for these compounds: a) in the bacteria, the compounds generate a cascade of events involving the inhibition of the respiratory chain complexes and energy production for efflux activity. Indirectly, this reduce the resistance level to antituberculosis drugs potentiating their activity; b) on the host cell, the treatment with the ion channel blockers increases phagosome acidification and induces the expression of phagosomal hydrolases, leading to bacterial growth restriction irrespective of their resistance pattern. This work highlights the potential value ion channel blockers as adjuvants of tuberculosis chemotherapy, in particular for the development of new therapeutic strategies, with strong potential for treatment shortening against drug susceptible and resistant forms of tuberculosis. Medicinal chemistry studies are now needed to improve the properties of these compounds, increasing their M. tuberculosis efflux-inhibition and killing-enhancement activity and reduce their toxicity for humans, therefore optimizing their potential for clinical usage.